2005
DOI: 10.1179/174367605x20171
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and characterisation of foam glass from cathode ray tubes

Abstract: Research into the recycling of electronics waste materials, such as cathode ray tubes (CRTs) and in particular their component glasses, is required by both French and European legislation. One possible solution to the problem of CRT glass waste is to convert it into foam glass, a material with very promising properties. Foam glasses can be prepared from CRT glasses containing heavy elements (lead, barium) through reaction with a reducing agent such as TiN or SiC. The present experimental study sought to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 9 publications
1
40
0
Order By: Relevance
“…Waste CRT, containing high content of Pb in the funnel glass (20-30% PbO [7]), has been listed by the China EPA as hazardous waste. It has been reported that this type of waste accounts for approximately 47% by weight of commercial electronic devices and 30% by weight of data processing equipment [8].…”
Section: Introductionmentioning
confidence: 99%
“…Waste CRT, containing high content of Pb in the funnel glass (20-30% PbO [7]), has been listed by the China EPA as hazardous waste. It has been reported that this type of waste accounts for approximately 47% by weight of commercial electronic devices and 30% by weight of data processing equipment [8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, many studies have been carried out on CRT glass treatments [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In previous years, CRT glass was generally cleaned, sorted and sent to glass manufacturers for new CRT glass manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…In previous years, CRT glass was generally cleaned, sorted and sent to glass manufacturers for new CRT glass manufacturing. Currently, due to the extreme reduction in CRT production, much attention had been attracted to the recycle of CRT glass as a secondary raw material, such as reutilization as glaze [4,5], glass ceramic [6], foam glass [7][8][9][10][11][12] and glass matrix composites [13][14][15][16]. Nevertheless, these methods paid little attention to the environmental security, since the prepared products still contain dangerous heavy metals, which should be removed or separated.…”
Section: Introductionmentioning
confidence: 99%
“…The cathode ray tube can be divided into three parts namely, (a) electron gun, (b) front panel glass, and (c) funnel glass. As containing high amount of lead, which necessary for absorbing the UV and X radiation produced by the electron gun, waste CRT funnel glass is considered as a hazardous waste [3]. Because broken lead containing glass will leach lead when mixed with acid water, land filling of this material is forbidden in most part of the world.…”
Section: Introductionmentioning
confidence: 99%